2019
DOI: 10.24996/ijs.2019.60.11.11
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of Peganum harmala L. callus to determine the gene expression of beta-carboline alkaloids harmine and harmaline

Abstract: The external signals are used as elicitors that can modify the levels of secondary metabolites production and trigger the biotechnological enforcements to improve plant production. In this study, sodium chloride NaCl was used as a stimulating factor for the production of beta-carboline alkaloids, harmine and harmaline, in Peganum harmala. The in vitro induced callus of P. harmalain was used as a source for alkaloid production in the stimulating experiments with sodium chloride. The results illustrated that 2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Total RNA was extracted from treated and untreated bacteria using the TRIzol TM Reagent (Thermo Scientific, USA) [26], and checked the purity and concentration using a Quantus Fluorometer (Promega, USA). We used the SYBER green dye's, one-step quantitative RT-PCR, GoTaq® Kit 1-Step RT-qPCR System, nuclease-free water, MgCL2 and Quantifluor RNA System (Promega, USA).…”
Section: Gene Expressionmentioning
confidence: 99%
“…Total RNA was extracted from treated and untreated bacteria using the TRIzol TM Reagent (Thermo Scientific, USA) [26], and checked the purity and concentration using a Quantus Fluorometer (Promega, USA). We used the SYBER green dye's, one-step quantitative RT-PCR, GoTaq® Kit 1-Step RT-qPCR System, nuclease-free water, MgCL2 and Quantifluor RNA System (Promega, USA).…”
Section: Gene Expressionmentioning
confidence: 99%
“…Moreover, Zanella et al [10] confirmed the correlation between high antioxidant activity and high phenolic content produced under various abiotic stresses in M. oleifera callus cultures. Substantially, many investigations regarded that using exogenous abiotic elicitors are very important to improve the valuable formation of secondary metabolites in medicinal plants [45,46].…”
Section: Dpph %mentioning
confidence: 99%
“…Genetic mutations and biotechnologies are being developed in response to the permitted opportunities provided by plant tissue culture for use in plant breeding and improvement. Where researchers' efforts have been combined in the study of plant cellular concepts in terms of their growth, development, and metabolic processes, and where these efforts have contributed to the formation of the concept of plant tissue culture and its effective role in genetic resource conservation, micropropagation, breeding, and plant improvement [1,2]. Climate change in arid and semi-arid areas, including Iraq, causes the annual loss of enormous amounts of agricultural land as a result of poor water management [ 2 ] .…”
Section: Introductionmentioning
confidence: 99%